Pemenuhan Meaningful Participation Sebagai Standar Konstitusional Good Governance - Agniski Pininta; Arinto Nurcahyono (Universitas Batanghari Jambi, 2026)
The principle of good governance requires democratic, transparent, and accountable governance, one of the ways to achieve which is through public involvement in public decision-making. In Indonesia, public participation is often still merely formalistic and has not yet resulted in substantial public involvement. Therefore, this article aims to analyze meaningful participation as a constitutional standard in the implementation of good governance. This study employs a normative legal methodology using a legislative, conceptual, and case-specific approach particularly analyzing Constitutional Court rulings regarding public participation in the formation and qualitative- normative analysis of such participation. The findings indicate that meaningful participation has become a constitutional standard demanding the fulfillment of the public’s right to be heard, considered, and provided with explanations regarding their opinions. This standard not only serves as a principle of procedural democracy but also as a tool for testing the constitutionality of the exercise of state power. Thus, strengthening meaningful participation is a primary requirement for realizing good governance that is in harmony with the principles of popular sovereignty and a democratic rule of law, as mandated by the 1945 Constitution.